65-39=26 so 26 employess dont have cellular phones. So 26/65 or in simplified form 2/5
9514 1404 393
Answer:
f^-1(x) = (x +4)/3
Step-by-step explanation:
The inverse function is found by swapping x and y, then solving for y.
y = 3x -4 . . . . . function y = f(x)
x = 3y -4 . . . . . inverse relation
x +4 = 3y . . . . add 4
(x +4)/3 = y . . . divide by 3. This is the inverse function
f^-1(x) = (x +4)/3
Answer:
he spent 48 dollars
Step-by-step explanation:
74-x=26
or
74-26=x
Slope = 4/1 = 4
hope it helps